2018
DOI: 10.1364/oe.26.003850
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion detector for range-resolved DIAL measurement of atmospheric CH4

Abstract: We demonstrate a robust, compact, portable and efficient upconversion detector (UCD) for a differential absorption lidar (DIAL) system designed for range-resolved methane (CH) atmospheric sensing. The UCD is built on an intracavity pump system that mixes a 1064 nm pump laser with the lidar backscatter signal at 1646 nm in a 25-mm long periodically poled lithium niobate crystal. The upconverted signal at 646 nm is detected by a photomultiplier tube (PMT). The UCD with a noise equivalent power around 127 fW/Hz o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Imaging is associated with the field of view (FOV) and the resolution of the detection system. Usually, the FOV of the scanning telescope has a wide range of 0.01-100 mrad [52][53][54]. As the FOV and the detection distance increase, the number of pixels receiving the TIR irradiance decreases.…”
Section: Infrared Optical Image Of the Sensormentioning
confidence: 99%
“…Imaging is associated with the field of view (FOV) and the resolution of the detection system. Usually, the FOV of the scanning telescope has a wide range of 0.01-100 mrad [52][53][54]. As the FOV and the detection distance increase, the number of pixels receiving the TIR irradiance decreases.…”
Section: Infrared Optical Image Of the Sensormentioning
confidence: 99%
“…The upconverted spectrum shows a good agreement with FTIR spectrum. Generally, upconversion detection gives a superior SNR at low signal levels (high absorbance's due to the very low dark noise in the Si detector) [28,29]. This is highly pertinent to the highly absorbing breast calcifications, and may allow for the use of thicker samples.…”
Section: Microcalcifications From An Ex Vivo Sample Of Breast Dcismentioning
confidence: 99%
“…4(c) is the angular profile of the USPDC photon count rate obtained by integrating Fig. 4(b) over the λ s axis (i.e., a range that, on the upconverted side, corresponds to the 635 ± 5 nm pass-band of the filter used in the experiment), and the blue dash curve is the |G(Δk d )| 2 [13], where G(Δk d ) is the Fourier transform of g(z), and Δk d is given by Eq. 2and Eq.…”
Section: Theorymentioning
confidence: 99%
“…In principle, we can further improve η up by increasing the pump power. Using a similar UCD design (Λ = 12.07 μm, λ s = 1646 nm), we have previously demonstrated that a 160 W pump with optimal spatial overlap with the signal can achieve η up as high as 45% [2]. In this work, a moderate pump power was used to maintain a stable operation of the UCD over the range of operating temperature in which USPDC noise was investigated.…”
Section: Signal-to-noise Ratio Improvement For Short-wavelength-pumpementioning
confidence: 99%
See 1 more Smart Citation